473 kV lightning impulse test of an insulator embedded in pressurized and heated liquid nitrogen - Stefan Fink; Sven Lautensack; Volker Zwecker (Institute of Advanced Engineering and Science, 2026)
Liquid nitrogen is the most common fluid for cooling superconducting power engineering devices. The dielectric strength of an insulator rod embedded in liquid nitrogen at a pressure of 0.3 MPa was investigated with lightning impulse voltage series of 20 impulses of ±473 kV for gap lengths up to 50 mm between a grounded plane and a high voltage electrode in the shape of a bell. The influence of boiling due to quenching of the superconductor was simulated by heating impulses with a duration of 10.1 s. Before triggering the heater impulse, the liquid nitrogen was in the subcooled state i.e., a pure liquid. Transient bubble generation due to the heater impulse was confirmed by video recording through an observation window of the cryostat. The voltage of 473 kV was kept by a gap length of 18 mm in case of impulses of positive polarity. A gap of 30 mm was necessary in case of negative polarity. Hence, a strong polarity effect was found. Calculated field values based on the experimental results do not exceed limits used for the high voltage design study for a support insulator of a superconducting fault current limiter.